Psychiatric disorders in children with demyelinating diseases of the central nervous system - Pakpoor, J; Goldacre, R; Schmierer, K; Giovannoni, G; Waubant, E; Goldacre, M (SAGE Publications, 2017)
The profile of psychiatric disorders associated with multiple sclerosis (MS) may differ in children. We aimed to assess the risk of psychiatric disorders in children with MS and other demyelinating diseases, and vice versa.We analyzed linked English Hospital Episode Statistics, and mortality data, 1999-2011. Cohorts were constructed of children admitted with MS and other central nervous system (CNS) demyelinating diseases. We searched for any subsequent episode of care with psychiatric disorders in these cohorts and compared to a reference cohort.Children with CNS demyelinating diseases had an increased rate of psychotic disorders (rate ratio (RR) = 5.77 (95% confidence interval (CI) = 2.48-11.41)); anxiety, stress-related, and somatoform disorders (RR = 2.38 (1.39-3.81)); intellectual disability (RR = 6.56 (3.66-10.84)); and other behavioral disorders (RR = 8.99 (5.13-14.62)). In analysis of the pediatric MS cohort as the exposure, there were elevated rates of psychotic disorders (RR = 10.76 (2.93-27.63)), mood disorders (RR = 2.57 (1.03-5.31)), and intellectual disability (RR = 6.08 (1.25-17.80)). In reverse analyses, there were elevated rates of a recorded hospital episode with CNS demyelinating disease after a previous recorded episode with anxiety, stress-related, and somatoform disorders; attention-deficit hyperactivity disorder (ADHD); autism; intellectual disability; and other behavioral disorders.This analysis of a national diagnostic database provides strong evidence for an association between pediatric CNS demyelinating diseases and psychiatric disorders, and highlights a need for early involvement of mental health professionals.